The Relationship between Iraqi EFL Preparatory School Teacher` Teaching Anxiety and the Mastery of Daily Lesson Plan - Khansa H. AL- Bahadli; Rasim T.Jehjooh (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Good teaching is the most basic important thing has teachers try to do in their classes and it is also in it the most frequently used language skills in communication activities. It plays an important role in the language learning process and facilitates the use of language skills. In this study the researchers tackled teaching anxiety that refers to the psychological response of a person to teaching task, which is determined by effect of feelings, believes and behaviors. And the relationship between teaching anxiety and the mastery of the daily lesson plan, which teaching means a system that enables a teacher to express himself/herself effectively with his/her interlocutors of a target language. The study questions are: Do Iraqi EFL preparatory school teachers have teaching anxiety? Do Iraqi EFL preparatory school teachers have mastery daily lesson plan? And is there any relationship between teaching anxiety and mastery daily lesson plan? Accordingly, the current study aims at finding out: Iraqi EFL preparatory school teachers’ teaching Anxiety level, Iraqi EFL preparatory school teachers’ mastery daily lesson plan level, and the relationship between Iraqi EFL preparatory School teachers` teaching anxiety and the mastery of the daily lesson plan. The sample of the present study consists of (30) male and female teachers from Iraqi EFL preparatory school teachers chosen randomly from Baghdad city.To achieve the aims of the present study, two instruments have been applied by the researchers, English Foreign language teaching anxiety scale and a English Foreign language lesson plan scale is constructed by the researchers themselves. After ensuring the validity and reliability of the instruments, the instruments have been applied and the data have been collected. Then a number of statistical tools have been used to analyze the obtained data.